Contextual housing environment and mental health of asylum seekers – a multi-level analysis. (30th September 2020) - Mohsenpour, A; Biddle, L; Bozorgmehr, K
Abstract: Background: Housing is an important determinant of health among asylum seekers and refugees (ASR). Little is known about the effects of contextual housing environment. We used state-wide reliable and valid data to examine these effects on ASR mental health. Methods: We drew a balanced random sample of 58 shared refugee accommodation centers (SRA) from 1938 centres with 70, 634 ASR in Germany's 3rd largest federal state. We measured depression (PHQ2) and anxiety (GAD2) using established instruments in nine languages. We assessed physical housing environment with a validated multi-dimensional Small-area Housing Environment Deterioration index (SHED). Linking survey- and SHED-data to GIS- and secondary data sources on accommodation size and remoteness, district urbanity and deprivation, we used multi-level logistic regression to calculate exposure effects and 95 % confidence intervals (CI), while adjusting for age, sex, relocations and chronic illness. Results: Of 412 ASR living in 58 SRA, 45.0% of inhabitants and 35.7% of SRA were rated as having a high/very high degree of deterioration. The odds for reporting symptoms of generalized anxiety increased for the highest degree of deterioration (1.30; 0.37-4.55), large accommodation size (1.01; 1.00-1.03), remoteness (1.63; 0.61 - 4.36), district urbanity (1.67; 0.66-4.20) and deprivation (1.33; 0.60-2.92). The odds of depression symptoms increased in SRA with highest deterioration (1.98; 0.74-5.33) and accommodation remoteness (1.10; 0.48-2.52), decreased in SRA with district urbanity (0.63; 0.31-1.28) and district deprivation (0.66; 0.36-1.23) but not large accommodation size (1.00; 0.99-1.02). Conclusions: Almost half of ASR are living in SRA with high/very high degree of deterioration. There is a general tendency of higher odds for mental illness symptoms conditional on housing environment. Future analyses with sample size calculations are needed to better understand these health associations for shared refugee accommodation. Key messages: We described contextual housing environment, i.e. degree of deterioration, accommodation size, remoteness, urbanity and deprivation, of a balanced random sample of 58 shared refugee accommodations. In multi-level logistic regression, contextual housing environment tends to be associated with higher odds for reporting symptoms of mental illness.